Antiepileptic drugs in Rett Syndrome. (July 2015) - Pintaudi, Maria; Calevo, Maria Grazia; Vignoli, Aglaia; Baglietto, Maria Giuseppina; Hayek, Yussef; Traverso, Maria; Giacomini, Thea; Giordano, Lucio; Renieri, Alessandra; Russo, Silvia; Canevini, MariaPaola; Veneselli, Edvige
Abstract Purpose We investigated drugs most often used to treat epilepsy in Rett Syndrome and their efficacy in a large cohort of Italian patients. Methods This is a multi-centre retrospective study. Data of 165 Rett subjects were collected from the patients' files, and hospital charts. The efficacy of antiepileptic drugs (AEDs) was classified as follows: not effective; decrease in seizure frequency ≥50% for at least 6 months; seizure-free for at least 2 years. Phenotypic and genetic categorization of patients was performed and it was considered in AEDs efficacy evaluation. Results There were 130 epileptic patients.Sodium valproate (VPA) was the most commonly administered AED (44.3%) at seizure onset, followed by Carbamazepine (CBZ) (25.4%) and Phenobarbital (PB) (13%). Monotherapy was the first treatment option in most patients. VPA and CBZ proved to be equally effective in Rett patients who presented seizures within the typical age range (4–5 years), while Lamotrigine (LTG) was effective for patients in whom epilepsy started later. Overall, the frequency of side effects was low and the most often observed ones were restlessness and somnolence. Conclusion Our study suggests that LTG, VPA and CBZ can be used as drugs of first choice in Rett Syndrome. The association of four drugs should be avoided since it did not result in any significant clinical improvement.